2022
DOI: 10.3389/fphar.2022.857502
|View full text |Cite
|
Sign up to set email alerts
|

Qingfei Litan Decoction Against Acute Lung Injury/Acute Respiratory Distress Syndrome: The Potential Roles of Anti-Inflammatory and Anti-Oxidative Effects

Abstract: Acute lung injury/acute respiratory distress syndrome (ALI/ARDS) is an acute respiratory failure syndrome characterized by progressive arterial hypoxemia and dyspnea. Qingfei Litan (QFLT) decoction, as a classic prescription for the treatment of acute respiratory infections, is effective for the treatment of ALI/ARDS. In this study, the compounds, hub targets, and major pathways of QFLT in ALI/ARDS treatment were analyzed using Ultra high performance liquid chromatography coupled with mass spectrometry (UHPLC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Current research has shown that TCM has an evident impact on the treatment of ALI induced by infectious diseases. For example, Qingfei Litan decoction has anti‐inflammatory and antioxidative effects on ALI (Diao et al, 2022). Xuebijing injection can significantly inhibit inflammatory and oxidative stress in ALI rats, and the effect is mainly related to mediating the downregulation of the TLR4 and NF‐ κ B expression (He et al, 2018; Xu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Current research has shown that TCM has an evident impact on the treatment of ALI induced by infectious diseases. For example, Qingfei Litan decoction has anti‐inflammatory and antioxidative effects on ALI (Diao et al, 2022). Xuebijing injection can significantly inhibit inflammatory and oxidative stress in ALI rats, and the effect is mainly related to mediating the downregulation of the TLR4 and NF‐ κ B expression (He et al, 2018; Xu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Natural herbal medicines, particularly traditional Chinese medicines (TCMs), are irrefutably precious resources for the exploration of new drugs for treating various intractable diseases ( 13 , 14 ). Increasing evidences have shown that TCMs could be used to improve COVID-19 pneumonia, and could be also effective to treat ARDS induced by various viruses or bacteria ( 15 - 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Network pharmacology is a combination of genomics, topology, systems biology, and other multidisciplinary and multiple techniques, which integrate the characteristics of integrity, dynamics and analysis in methodology, and is similar to the synergistic action of traditional Chinese medicine through principal, assistant, complement and guide [12,13]. Therefore, it has been widely used in the study of the pharmacological mechanism of Chinese traditional compound medicine [14][15][16]. Molecular docking technology, which uses computer-assisted drug design, is a well-established method to assist in small molecule drug development [17][18][19].…”
Section: Introductionmentioning
confidence: 99%